2014
DOI: 10.3389/fpls.2014.00727
|View full text |Cite
|
Sign up to set email alerts
|

Plant grafting: new mechanisms, evolutionary implications

Abstract: Grafting, an old plant propagation practice, is still widely used with fruit trees and in recent decades also with vegetables. Taxonomic proximity is a general prerequisite for successful graft-take and long-term survival of the grafted, composite plant. However, the mechanisms underlying interspecific graft incompatibility are as yet insufficiently understood. Hormonal signals, auxin in particular, are believed to play an important role in the wound healing and vascular regeneration within the graft union zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
266
0
25

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(294 citation statements)
references
References 119 publications
(181 reference statements)
3
266
0
25
Order By: Relevance
“…Kester and Hansen (1964) reported that almond cultivars and selections grafted on 'Marianna 2624' exhibited different behaviors, from lack of symptoms up to full incompatibility, six years after field planting, and Grasselly (1983) reported that some 'Myrobalan' clones (P. cerasifera) showed graft compatibility with various peach cultivars. Even though early detection of graft incompatibility has been reported (RODRIGUES et al, 2001;ERREA;BORRUEY, 2004;ZARROUK et al, 2006b;ZARROUK et al, 2010), the methods usually have limitations and evaluation cycles in the field for some rootstock combinations may require several years before any assumptions on compatibility and yield efficiency can be made, especially when genotypes are taxonomically distant (GOLDSCHMIDT, 2014). Thus, graft incompatibility is one of the major hurdles for rootstock improvement and analysis (CIOBOTARI et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kester and Hansen (1964) reported that almond cultivars and selections grafted on 'Marianna 2624' exhibited different behaviors, from lack of symptoms up to full incompatibility, six years after field planting, and Grasselly (1983) reported that some 'Myrobalan' clones (P. cerasifera) showed graft compatibility with various peach cultivars. Even though early detection of graft incompatibility has been reported (RODRIGUES et al, 2001;ERREA;BORRUEY, 2004;ZARROUK et al, 2006b;ZARROUK et al, 2010), the methods usually have limitations and evaluation cycles in the field for some rootstock combinations may require several years before any assumptions on compatibility and yield efficiency can be made, especially when genotypes are taxonomically distant (GOLDSCHMIDT, 2014). Thus, graft incompatibility is one of the major hurdles for rootstock improvement and analysis (CIOBOTARI et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…A common form of incompatibility is "translocated" incompatibility, in which symptoms occur during plant development, and include early termination of scion and root growth, shriveling and early leaf drop, reduced carbohydrate translocation between scion, and rootstock leaf chlorosis evolving to leaf reddening. Thus, the appropriate choice of scion/ rootstock combination is key to achieving graft compatibility (MOSSE, 1962;HARTMANN et al, 2002;GOLDSCHMIDT, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A decisive factor in the failure of grafts is incompatibility, which refers to the lack of union between stock and scion, which affects the growth and productivity of the plants, and may even lead to their death [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Hormonal signals, auxin in particular, are believed to play an important role in the wound healing and vascular regeneration within the graft union zone (Pina, Errea 2005;Goldschmidt 2014), as well as profoundly influence root morphology, increasing lateral root production and inducing adventitious roots (Aloni et al 2006;Overvoorde et al 2010;Woodward, Bartel 2005). The present data as well confirm the influence of exogenous auxin application on adventitious root formation and root architecture in the rootstocks of root pruned splice grafted (RPSG) cucumber seedlings.…”
Section: Resultsmentioning
confidence: 99%